2022
DOI: 10.1002/jcsm.13030
|View full text |Cite
|
Sign up to set email alerts
|

An umbrella review of systematic reviews of β‐hydroxy‐β‐methyl butyrate supplementation in ageing and clinical practice

Abstract: The compound β-hydroxy-β-methyl butyrate (HMB) is proposed to increase or mitigate the loss of skeletal muscle and improve muscle function. We undertook a review of systematic reviews of HMB supplementation to promote gains or mitigate muscle loss in ageing and clinical populations. Following PRISMA guidelines, we searched for systematic reviews reporting the effect of HMB in our target populations. Dual-energy X-ray absorptiometry (DXA) measured lean soft-tissue mass (LSTM) was accepted as a proxy for muscle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The methodological quality of all included reviews was determined in duplicate using A Measurement Tool to Assess Systematic Reviews (AMSTAR), 9 as previously described, 10 , 11 to yield a score ranging from 1 to 11. Three authors (BSC, CVL, and JCM) systematically synthesized the evidence from each review to produce a standardized effectiveness statement (sufficient evidence, some evidence, insufficient evidence, insufficient evidence to determine; see Supplementary Table 2 ) for each outcome.…”
Section: Methodsmentioning
confidence: 99%
“…The methodological quality of all included reviews was determined in duplicate using A Measurement Tool to Assess Systematic Reviews (AMSTAR), 9 as previously described, 10 , 11 to yield a score ranging from 1 to 11. Three authors (BSC, CVL, and JCM) systematically synthesized the evidence from each review to produce a standardized effectiveness statement (sufficient evidence, some evidence, insufficient evidence, insufficient evidence to determine; see Supplementary Table 2 ) for each outcome.…”
Section: Methodsmentioning
confidence: 99%
“…HMB has been shown to have anabolic and anti-catabolic effects in human skeletal muscle (Wilkinson et al 2013 , 2018 ). However, controversy still exists as to whether these properties can be translated into benefits for athletic populations, although emerging evidence suggest benefits for clinical populations under muscle wasting conditions (Tritto et al 2019 ; Jakubowski et al 2020 ; Phillips et al 2022 ; Wu et al 2015 ; Bear et al 2019 ). It has been argued that the effectiveness of HMB is linked to its pharmacokinetics properties, with current knowledge indicating that HMB-FA is the preferred form due to its superior bioavailability (Wilkinson et al 2013 ; Wilson et al 2013a , b , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human studies showed that HMB can counteract age-related muscle loss (Oktaviana et al 2019 ) and muscle wasting in conditions such as bed rest (Deutz et al 2013 ) and cancer (Clark et al 2000 ). The potentially beneficial effects of HMB supplementation on muscle strength and muscle mass in conditions of exacerbated muscle loss has been supported by meta-analyses (Wu et al 2015 ; Bear et al 2019 ), although controversy still exists as to whether HMB can effectively support muscle growth in healthy individuals undergoing resistance training, with current evidence not supporting its use for enhancing training adaptations in young, healthy, trained individuals (Tritto et al 2019 ; Jakubowski et al 2020 ; Phillips et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the inconsistent results of previous studies on the benefits of protein supplementation on skeletal muscle mass and function in the elderly, it is still unclear if it is necessary or should be increased [9]. Notably, contradictory results have been reported in recent study on the effect of HMB on improving skeletal muscle mass and function in older individuals [10]. Although vitamin D supplementation has been shown to increase muscle mass in older individuals, the exact dosage, frequency, and length of treatment are unknown [9].…”
Section: Introductionmentioning
confidence: 99%